Comparison of the revised 4th (2016) and 5th (2022) editions of the World Health Organization classification of myelodysplastic neoplasms - Zhang, Yudi; Wu, Junying; Qin, Tiejun; Xu, Zefeng; Qu, Shiqiang; Pan, Lijuan; Li, Bing; Wang, Huijun; Zhang, Peihong; Yan, Xin; Gong, Jingye; Gao, Qingyan; et al. (Leukemia, 2022)
We used data from 852 consecutive subjects with myelodysplastic neoplasms (MDS) diagnosed according to the 2016 (revised 4th) World Health Organization (WHO) criteria to evaluate the 2022 (5th) edition WHO classification of MDS. 30 subjects previously classified as MDS with an NPM1 mutation were re-classified as acute myeloid leukaemia (AML). 9 subjects previously classified as MDS-U were re-classified to clonal cytopenia of undetermined significance (CCUS). The remaining 813 subjects were diagnosed as: MDS-5q ( N = 11 [1%]), MDS-SF3B1 ( N = 70 [9%]), MDS-biTP53 ( N = 53 [7%]), MDS-LB ( N = 293 [36%]), MDS-h ( N = 80 [10%]), MDS-IB1 ( N = 161 [20%]), MDS-IB2 ( N = 103 [13%]) and MDS-f ( N = 42 [5%]) and MDS-biTP53 ( N = 53 [7%]). 34 of these subjects came from the 53 (64%) MDS-biTP53 previously diagnosed as MDS-EB. Median survival of subjects classified as MDS using the WHO 2022 criteria was 45 months (95% Confidence Interval [CI], 34, 56 months). Subjects re-classified as MDS-biTP53 and MDS-f had significantly briefer median survivals compared with other MDS sub-types (10 months, [8, 12 months] and 15 months [8, 23 months]). In conclusion, our analyses support the refinements made in the WHO 2022 proposal.